Kajian Docking 3-[(Asetiloksi)Metil]-7-[(4-Hidroksi-3-Metoksifenil)Metilidin]Amino]-8-Okso-5-Thia 1-Azabisiklo[4.2.0]Oct-2-Ene-Asam Karboksilat Menggunakan Dock6 - Artinda, Syafira Amalia (2016)
New design of powerful antibiotics to treat antibiotic resistance is by combining natural compounds with existing antibiotics. 7-Aminocephalosporins acid the derivative of cephalosporin will combine with natural materials such as vanillin, has result 3-[(acetyloxy)methyl]-7-[[(4-hydroxy-3-ethoxyphenyl)methylidene]amino]-8-oxo-5-thia-1-azabicyclo[4.2.0]oct-2-ene-2-carboxylic acid or KH2013C through addition elimination reaction. KH2013C have an imine in structure, different with another cephalosporin derivate which have an amide groups. Molecular docking performed an approximate positioning, orientation and conformation of a ligand binding to the target protein. 10 PDB ID as a target protein of PBP, KH2013C as test ligands and other derivatives cephalosporins (Cephalexin, Cefaclor, Ceftriaxone and Cefpirome) as a comparator ligands used in the study. There are 3 PDB having grid scores more negative than the native ligand there are 3UDF -38,92253 kkal/mol; 3MZD -48,9805kkal/mol; and 2Y2P -50,4182kkal/mol. Test ligand has a better bond with the amino acid because the grid scores more negative than the native ligand, but it has different amino acid all because having binding site pocket larger